Non infectious risk factors in pediatric sensorineural hearing loss - Bambang Udji Djoko Rianto; Bondan Herwindo; Ashadi a Prasetyo; Anggoro Eka Radity (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2017)
Pediatric sensorineural hearing loss can cause delay in speech and daily socialcommunication. The causative factors are infectious or non infecious. The role ofinfectious risk factors in pediatric sensorineral hearing loss has been proven. However,the role of non infectious factors has not been reported, yet. The aim of the study was toevaluate the role of non infectious factors in pediatric sensorineural hearing loss (SNHL).This was a case control study using data collected from outpatients and medical recordsin Dr. Sardjito General Hospital, Yogyakarta from June to December 2015. The inclusioncriteria of case group were children with SNHL and aged 0 – 5 years old, whereasthe inclusion criteria of control group was children with normal hearing and aged 0-5years old. The exclusion criteria were children with history of infectious risk factors andhead trauma. Hearing status were determined by Otoacoustic Emission Testing (OAE)and Brainstem Evoked Response Auditory (BERA), based on a= 5%, b = 20%; ORasumption = 3.0. Sixty two subjects were selected with 31 subjects in each group.Multivariate analysis showed that low birth weight (LBW) (p=0.018; OR=6.553; 95%CI=1.38 – 31.13) and asphyxia (p= 0.041; OR=6.448; 95% CI=1.077 – 38.595)were risk factors, while hyperbilirubinemia (p= 0.382; OR=2.46; 95% CI=0.365 –13.805) and gestation (p=0.876; OR=0.831; 95% CI=0.081 – 8.483) were not riskfactors for pediatric SNHL. In conclusion, LBW and asphyxia are risk factors for pediatricSNHL, whereas prematurity and hyperbilirubinemia are not risk factors.